Genomic analysis finds no evidence of canonical eukaryotic DNA processing complexes in a free-living protist - Salas-Leiva, Dayana E; Tromer, Eelco C; Curtis, Bruce A; Jerlström-Hultqvist, Jon; Kolisko, Martin; Yi, Zhenzhen; Salas-Leiva, Joan S; Gallot-Lavallée, Lucie; Williams, Shelby K; Kops, Geert J P L; Archibald, John M; Simpson, Alastair G B; et al. (Nature communications, 2021)
Cells replicate and segregate their DNA with precision. Previous studies showed that these regulated cell-cycle processes were present in the last eukaryotic common ancestor and that their core molecular parts are conserved across eukaryotes. However, some metamonad parasites have secondarily lost components of the DNA processing and segregation apparatuses. To clarify the evolutionary history of these systems in these unusual eukaryotes, we generated a genome assembly for the free-living metamonad Carpediemonas membranifera and carried out a comparative genomics analysis. Here, we show that parasitic and free-living metamonads harbor an incomplete set of proteins for processing and segregating DNA. Unexpectedly, Carpediemonas species are further streamlined, lacking the origin recognition complex, Cdc6 and most structural kinetochore subunits. Carpediemonas species are thus the first known eukaryotes that appear to lack this suite of conserved complexes, suggesting that they likely rely on yet-to-be-discovered or alternative mechanisms to carry out these fundamental processes.
Keywords: mikrobiologie; Proteins; DNA; Biological Evolution; Microbiology; genomika; genom; eukaryotické buňky; Animals; Eukaryotic Cells; Genome; proteiny; Genomics; zvířata; Eukaryota; biologická evoluce; Parasites; paraziti